A Feminist Stylistic Analysis In Jessica Knoll's Novel Luckiest Girl Alive - Ahmad Haris Hutasuhut; Rahmadsyah Rangkuti (Talenta Publisher, 2022)
This study aims to examine how the use of linguistic stylistics in describing women in a text. This study uses a feminist stylistic approach, which in this case focuses more on applying different perspectives to gender-specific women and men. The data in this study are in the form of words, phrases or sentences, and discourses that indicate gender-specific and are taken from Jessica Knoll's novel entitled Luckiest Girl Alive. Each of these levels describes how the gender presentation of feminism can be obtained and can also be seen as a feminist trait. The application of feminist stylistic theory proposed by Sarah Mills in this study shows that female characters are described as being so different from men, women are depicted based on their body parts, experiences, emotions, vulnerability to men, and even female characteristics in general. While men are described based on their physical strength, attitudes, personality, and also their dominance over women. This research helps the readers to reduce errors in understanding gender-specific coding in the form of words, phrases or sentences, and discourse in general or in detail.